LOCATIONAL AGREEMENT OF NEAR-INFRARED AUTOFLUORESCENCE WITH CHOROIDAL VASCULAR HYPERPERMEABILITY IN CENTRAL SEROUS CHORIORETINOPATHY. Issue 11 (November 2022) - Azuma, Keiko; Nomura, Yoko; Kitamoto, Kohdai; Hashimoto, Yohei; Fujino, Ryosuke; Ueda, Kohei; Inoue, Tatsuya; Obata, Ryo
Abstract : This study reports the locational agreement between multimodal imaging findings and choroidal vascular hyperpermeability in central serous chorioretinopathy. The near-infrared autofluorescence imaging findings corresponded well with the site of choroidal vascular hyperpermeability. Moreover, binarization of the near-infrared autofluorescent dark dots area corresponded well with that of choroidal vascular hyperpermeability. Abstract : Purpose: To characterize the findings of eyes with choroidal vascular hyperpermeability (CVH), a hallmark of central serous chorioretinopathy, using multimodal imaging and investigate the locational agreement between these findings and CVH. Methods: Among patients with central serous chorioretinopathy in either eye, eyes with CVH identified using indocyanine green angiography without exudative changes were included. All eyes were examined using funduscopy, fluorescein angiography, spectral-domain optical coherence tomography, and short-wavelength or near-infrared autofluorescence (SWAF or NIRAF). The locational agreement between CVH and imaging findings was evaluated for each modality. The relative index on how they overlapped was calculated as the overlapping index. Binarized images, particularly for NIRAF, were also evaluated. Results: This study included 69 CVH sites in 33 eyes of 28 patients. Pachydrusen was detected in 36% of CVH sites. Fluorescein angiography revealed hyperfluorescent areas in 39% of CVH sites. Optical coherence tomography findings identified 65% of CVH sites, but the overlapping index was 5%. Short-wavelength or near-infrared autofluorescence imaging identified 89% of CVH sites, but they exhibited variable autofluorescence. NIRAF imaging revealed hypoautofluorescence findings in all CVH sites. When binarized, near-infrared autofluorescent dark dots were observed in all CVH sites. Overlapping indices before and after binarization were 78% and 98%, respectively. The near-infrared autofluorescent dark dots area corresponded well with that of CVH (intraclass correlation coefficient, 0.987 [95% confidence interval, 0.952–0.995]). Conclusion: Hypoautofluorescent findings revealed on NIRAF imaging, especially after binarization processing, corresponded well with CVH sites. These multimodal imaging results may help investigate the anatomical or locational characteristics of CVH in patients with central serous chorioretinopathy.